Cayman Islands : Off-shore Financial Center Assessment Update-Assessment of Financial Sector Supervision and Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses findings of the assessment of Financial Sector Supervision and Regulation on the Cayman Islands. The assessment reveals that substantial progress has been made in the implementation of the 2003 Offshore Financial Center assessment recommendations, including, importantly, regarding Cayman Islands Monetary Authority's independence and resources. There is scope for enhancing regulatory reporting and disclosure requirements by financial entities, such as shortening the period for filing required documents and requiring all insurers to disclose their use of derivatives and similar commitments regularly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet